Recent Trends of Seroprevalence of Dengue in a Tertiary Care Hospital in Southern Odisha - Susmita Kumari Sahu; Sanoj Pasupalak; Indrani Mohanty; Moningi Venkata Narasimham (Journal of Clinical and Diagnostic Research, 2018)
Introduction: Dengue is a most common arthropod borne viral infection. It is endemic in several parts of India. It can lead to life threatening severe complications such as Dengue Haemorrhagic Fever (DHF)/Dengue Shock Syndrome (DSS). Aim: This study was conducted to know the seroprevalence of Dengue virus in a tertiary care hospital, Berhampur, Southern Odisha, India. Materials and Methods: Over a period of four years from January 2013 to December 2016, a total of 7345 blood samples from clinically suspected dengue patients were received in department of Microbiology laboratory. Serum was separated and subjected to enzyme immunoassay for detection of both Non Structural (NS1) antigen and IgM antibody. Results: Out of 7345 serum samples positive infection detected in 712 (9.6%) cases. Maximum number of cases were detected in the year 2016 and less number of cases were detected in 2013. Majority numbers of cases were detected in the month of September. Combination of NS1Ag ELISA and IgM antibody ELISA were used for early detection of dengue infection. Conclusion: Regular epidemiological studies are necessary to monitor the dengue situation in an area which helps in early detection of an outbreak and to initiate effective control measures.